2016
DOI: 10.1002/biot.201600360
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of donor sources and media influence the histo‐morphological quality of full‐thickness skin models

Abstract: Human artificial skin models are increasingly employed as non-animal test platforms for research and medical purposes. However, the overall histopathological quality of such models may vary significantly. Therefore, the effects of manufacturing protocols and donor sources on the quality of skin models built-up from fibroblasts and keratinocytes derived from juvenile foreskins is studied. Histo-morphological parameters such as epidermal thickness, number of epidermal cell layers, dermal thickness, dermo-epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…However, while keratinocytes isolated from neonatal foreskin had a higher rate of proliferation compared to cells isolated from adult skin, the differences in the proliferation of fibroblasts could not be associated with age, gender or anatomical location, but it was rather donor specific. Accordingly, Lange et al showed that optimal culture conditions to generate skin models may differ depending on the cell source 68 . The donor‐to‐donor variability is a key point in the development of tissue engineered models using primary cells for regenerative medicine and fabrication of in vitro models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while keratinocytes isolated from neonatal foreskin had a higher rate of proliferation compared to cells isolated from adult skin, the differences in the proliferation of fibroblasts could not be associated with age, gender or anatomical location, but it was rather donor specific. Accordingly, Lange et al showed that optimal culture conditions to generate skin models may differ depending on the cell source 68 . The donor‐to‐donor variability is a key point in the development of tissue engineered models using primary cells for regenerative medicine and fabrication of in vitro models.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Lange et al showed that optimal culture conditions to generate skin models may differ depending on the cell source. 68 The donor‐to‐donor variability is a key point in the development of tissue engineered models using primary cells for regenerative medicine and fabrication of in vitro models. These observations demonstrate the importance of using a representative cell population for the optimization of biomaterials for tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…We employed both a collagen skin model under static conditions and a vascularized skin model under dynamic conditions in a bioreactor system (Groeber et al, 2016a;Rossi et al, 2015;Lange et al, 2016). Pre-stimulated or unstimulated randomly HLA-mismatched lymphocytes injected either directly into the model or into the circulation medium induced a histomorphological pattern typical for GvHD.…”
Section: Discussionmentioning
confidence: 99%
“…Human full-thickness skin models were generated based on a collagen hydrogel in 24-well inserts (Polycarbonate Membrane Inserts in Multidish 24, Nunc™, Roskilde, Denmark) according to a previously published protocol using the EpiLife ® medium system (Lange et al, 2016). Briefly, 500 µl dermal equivalents were prepared by mixing 5x10 4 fibroblasts per insert with the collagen solution (collagen solution prepared in-house, 4 mg/mL final rat-tail collagen type I concentration).…”
Section: Cell Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation